Renal autotransplantation in a child following renal artery stent fracture - Mukut Minz; A Sharma; S Kumar; S Singh (Wolters Kluwer Medknow Publications, 2011)
We report an 8-year-old child who underwent percutaneous transluminal renal angioplasty (PTRA) and stenting for renal artery stenosis (RAS) and later presented with stent fracture. Ex vivo renal artery repair and renal autotransplantation were successfully done.